Use of murinometrics indices and bioelectrical impedance (BIA) in the determination of experimental obesity in oophorectomized rats - Ferraz, Alex Soares Marreiros; Moraes, Ruan Carlos Macêdo de; Sá, Naiza Arcângela Ribeiro de; Andrade, Francisco Teixeira; Martins, Maria do Carmo de Carvalho e; Ceccatto, Vânia Marilande (Acta Scientiarum. Biological Sciences, 2016)
In this study, we tested the use of murinometric indices and bioimpedance (BIA) to determine obesity in rats. Female Wistar rats (8 weeks/130-160 g) were divided into control and oophorectomy group. The Body Mass Index (BMI) and Lee index (LI) were used as anthropometric techniques to determine obesity, and the determination of body composition by BIA, as a way to partition body weight into fat mass and lean mass components. The dissection of muscle tissues and adipose deposits was used as a direct determination of body fat content. The groups had body weight gain (p <0.05) after the trial period, with a differential gain in body fat (p <0.05) observed by the dissection of tissue in the oophorectomy group. This gain in body fat was detected more accurately by BIA, due to the greater ability of this method to distinguish lean from fat mass. BIA was able to measure the differential gain of body fat in a BMI considered as eutrophic by murinometric indices.